Shelf-life estimation of dried pasta based on sago starch and oyster mushroom powder using a critical water content model - Rahmawati Rahmawati; Evy Damayanthi; Budi Setiawan; Eny Palupi (Arsip Keilmuan Gizi (AKG), 2025)
Dry pasta, such as spaghetti, is a hygroscopic food product susceptible to quality degradation due to moisture absorption from the environment. This study aims to predict the shelf life of an innovative dry pasta made from a sago starch and oyster mushroom composite using the critical moisture content method (Labuza Model). The shelf life estimation was conducted based on the Labuza equation with input parameters including an initial moisture content (Mi) of 0.139 g/g solids, equilibrium moisture content (Me) of 0.218 g/g solids, and critical moisture content (Mc) of 0.164 g/g solids. The product was packaged in aluminum foil with an effective surface area (A) of 0.024 m² and a packaging permeability (k/x) of 0.024 g/day.m².mmHg. The results showed that at a storage temperature of 30 °C with a saturated vapor pressure of 31.80 mmHg and a slope value (b) of 0.227, the product has a predicted shelf life of 11.86 months (355.89 days). These findings indicate that the use of aluminum foil packaging is effective in maintaining the quality of sago starch and oyster mushroom-based pasta for long-term storage.